Government policy responses and stock liquidity: covid-19 pandemic - Yee-Ee Chia; Mohd Ashari Bakri; Eva Nur (Human Resource Management Academic Research Society, 2025)
The COVID-19 pandemic has caused huge disruptions in global economies, and a government is needed to implement different degrees of stringency measures to prevent the virus’s spread. This study examines the impact of government policy responses on stock liquidity in Malaysia during the COVID-19 pandemic. The sample period covered from January 2, 2020 to June 30, 2022, comprising 890 publicly traded stocks, disaggregated into 539 large and 351 small capital stocks. The pooled ordinary least squares results show that the government policy announcement has significantly improved liquidity in Malaysia’s financial market. Hence, our findings demonstrate that restrictions and policies taken by the government are important for policymakers and financial institutions to mitigate liquidity challenges amidst heightened uncertainty and market volatility during the coronavirus outbreak.